SISTEM INFORMASI FITOFARMAKA (SIFITA) BERBASIS WEB SEBAGAI SUMBER INFORMASI APOTEKER - Sri Suwarni; Timmy Gondo Atmodjo; Pertiwi Setyaningrum; Gilang Rizki Al Farizi (Jurnal Kesehatan Tambusai, 2023)
Pharmaceutical services are a direct and responsible form of service for pharmacists in Indonesia to provide pharmaceutical preparations to patients. One of the pharmaceutical preparations given is traditional medicine. Phytopharmaca is a form of traditional Indonesian medicine that comes from plants that have undergone pre-clinical trials and clinical trials that can be submitted by pharmaceutical staff. In the Era 4.0 of the industrial revolution, it is very possible for services to be made easier when accessing information systems because it is faster so that it can maintain patient trust. Advances in technology in all fields can bring many benefits, one of which is in the pharmaceutical world. The information system was built on a web basis so that it is easy to use because it can be accessed via various electronic media such as laptops, PCs or gadgets and can be accessed at any time via the internet network. With this convenience, many users from pharmaceutical and non-pharmaceutical personnel will be able to get information from phytopharmacies circulating on the market. The aim of this research is to create a web-based information system as a source of information for pharmaceutical staff about Phytopharmaca. The research design was experimental, descriptive qualitative with a triangulation method by means of observation, interviews and official literature review in FGD. The instrument used is a Depth Interview sheet which has been reviewed by experts. The result of this research is a Web-based Information System which contains content regarding Phytopharmaca as a source of information for pharmaceutical personnel with features that pay attention to content, format, accuracy and ease of use with the name SIFITA. The menu in SIFITA is a list of phytopharmaca, phytopharmaca product gallery, profile, contact, knowledge about phytopharmaca complete with photos and regulations which can be downloaded.